Lymphogranuloma venereum (LGV) of the anorectum: evaluation of clinicopathological associations and the utility of a novel RNA in‐situ hybridisation stain. Issue 3 (14th October 2020) - Waters, Kevin M; Cox, Brian K; Wong, Mary T; Guindi, Maha; Kim, Stacey A; Larson, Brent K; Morgan, Margie; Voltaggio, Lysandra; Balzer, Bonnie L
Abstract : Aims: Recent studies from multiple global regions have reported a resurgence of lymphogranuloma venereum (LGV) proctitis, which is caused by Chlamydia trachomatis (CT). LGV proctitis is histologically indistinguishable from other forms of sexually transmitted proctitis and is difficult to differentiate from inflammatory bowel disease. While immunohistochemical stains are available for syphilis, there is no commonly available stain for the tissue identification of CT. Materials and methods: From 200 positive CT nucleic acid tests (NAT) from anorectal swabs, we identified 12 patients with biopsies collected from the distal colorectum or anus within 90 days of the positive NAT. We collected basic demographic information and tabulated clinical and histological findings. We examined the performance of a novel RNA in‐situ hybridisation (ISH) stain targeting CT 23s rRNA on these 12 cases and 10 controls from the anorectum. Results: All 12 patients were male; nine were HIV+, two had concurrent gonococcal infection, one had concurrent syphilis and one had cytomegalovirus co‐infection. The majority of biopsies (11 of 12) showed mild or moderate acute inflammation, had a prominent lymphoplasmacytic infiltrate (eight of 11) and lacked marked crypt distortion (10 of 10). The RNA ISH stain was positive in 10 of 12 cases (sensitivity 83%). One case showed equivocal staining. No controls showed definitive positive staining (specificity 100%). One had equivocal staining. Conclusion: Our series showed that anorectal LGV had similar histological findings to those of prior STI proctitis series predominantly comprised of syphilis. The novel RNA ISH stain was sensitive and specific and may show utility in differentiating types of STI proctitis.